Comprehensive analysis of skin growth-related hub genes and microenvironment characterization in a mouse expanded skin model - Wang, Yinmin; Qi, Wenxiao; Yu, Shun; Zhou, Xianyu; Wang, Xiuxia; Liu, Fei; Jin, Rui; Luo, Xusong; Ma, Qiangliang; Lu, Lin; Yang, Jun (Frontiers in Immunology, 2024)
BackgroundMechanical stretch-mediated tissue expansion is effective for obtaining extra skin and soft tissue required for the repair of defects or reconstruction of surface organs. Understanding the cellular and molecular mechanisms and identifying hub genes and key cell types associated with skin expansion could help predict the success of skin growth during expansion procedures.MethodsWe analyzed murine chip sequencing data and single-cell sequencing data available from the Gene Expression Omnibus database. Based on the differentially expressed and epithelial–mesenchymal transition-related genes, random forest and protein-protein interaction network analysis identified hub genes for predicting skin regeneration in tissue expansion. The fate of the cell subpopulations, expression of hub genes in different cell types, and their communication were also assessed.ResultsFive genes, integrin beta 5 (Itgb5), tropomyosin 1 (Tpm1), secreted frizzled-related protein-1 (Sfrp1), Notch1, and insulin-like growth factor binding protein 2 (Igfbp2), were identified as having the greatest impact on prediction accuracy. These hub genes were primarily enriched in the Notch and phosphoinositide 3-kinase-AKT pathways. Immune cell infiltration analysis further revealed that mast cell infiltration was significantly higher in the expanded skin group than that in the control group. According to single-cell data, the interactions between epithelial cells, stem cells, and other cell types were higher in the expanded skin group than those in the control group. Moreover, Tpm1, Sfrp1, and Notch1 were highly expressed in all epithelial and stem cell subgroups.ConclusionsThe hub genes, Notch1, Tpm1 and Sfrp1, and their associated signaling pathways such as Notch and Wnt signaling and functions in key cell subsets highlight prospective therapeutic strategies to enhance skin growth under mechanical expansion. Moreover, mast cell activation and infiltration may trigger immune responses in the expanded skin, which requires further investigation.